2012
DOI: 10.1093/bja/aes209
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with intrathecal or intravenous morphine attenuates hepatic ischaemia–reperfusion injury in normal and cirrhotic rat liver

Abstract: † Opioid preconditioning protects against ischaemia -reperfusion injury (IRI) in many organs. † Morphine given i.v. or intrathecally protected against IRI in both normal and cirrhotic rat liver. † This effect required peripheral m-opioid receptor activation and multiple prosurvival intracellular signalling pathways. † Further studies are required to establish the clinical significance of these effects.Background. Opioids have been shown to attenuate ischaemia-reperfusion injury (IRI) in a number of organs. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In rat liver, morphine preconditioning protects against IRI. This involves opioid receptors, phosphatidylinositol 3-kinase, and Akt [41] . IP protected against hepatic IRI under isoflurane anesthesia in rats.…”
Section: Intraoperative Featuresmentioning
confidence: 99%
“…In rat liver, morphine preconditioning protects against IRI. This involves opioid receptors, phosphatidylinositol 3-kinase, and Akt [41] . IP protected against hepatic IRI under isoflurane anesthesia in rats.…”
Section: Intraoperative Featuresmentioning
confidence: 99%
“…The mechanisms of morphine-induced hepato-protection are most likely multifactorial. These multifactorials involve opioid receptors, phosphatidylinositol-3-kinase, and Akt [11]. …”
Section: Opioids (Morphine Remifentanil and Fentanyl)mentioning
confidence: 99%
“…When blood reflows after a long interruption, recruited neutrophils aggressive hepatocytes directly. Numerous methods are reported to attenuate hepatic IRI including ischemic pretreatment, ischemic postconditioning and medication pretreatment [4][5][6][7]. To treat all patients in clinics and set up more efficient therapeutic methods, more clinical studies are required Neural axis analgesia is a common technique used for patients undergoing abdominal surgery [8].…”
Section: Introductionmentioning
confidence: 99%
“…Intrathecal morphine pretreatment has been showed to protect myocardial IRI [9,10]. Our previous study has demonstrated intrathecal morphine pretreatment (MPC) is necessary to have protective effects for hepatic IRI [6]. However, the related mechanisms of intrathecal MPC on hepatic IRI remain to investigate.…”
Section: Introductionmentioning
confidence: 99%